Income Distribution in Peru, 1996-1999 - Quispe Llanos, Renán (2005)
The unequal distribution of income and the high levels of poverty, determine that in our society limitations are observed for a more constant and equitable development and reduce access to education, health and better living standards. On the other hand, in the modern concept of development, the growth of a country is not enough, if imbalances and inequalities are not simultaneously shortened in the search for a more lasting economic, political and social well-being.